Addition of gaseous olefin to produce boiler fuel and stability studies. Issue 3 (2nd December 2014) - Tao, Jingming; Penmetsa, Venkata K.; Steele, Philip H.
<x xml:space="preserve">Abstract</x> As a renewable liquid fuel, bio‐oil produced from fast pyrolysis of biomass is receiving increasing attention. However, bio‐oil has some negative properties, such as polymerization over time, high water content, high viscosity, and low energy value. It must be upgraded to be used as a fuel. The objective of this study was to develop an upgrading method by esterification and olefination reactions to produce bio‐oil with lower water content and higher energy value for combustion as a boiler fuel. Loblolly pine wood was pyrolyzed at a feed rate of ∼7 kg/h in a Mississippi State University proprietary auger reactor to produce bio‐oil with 65% yield. Upgrading reactions were performed in a high‐pressure batch autoclave. Bio‐oil was reacted with alcohols and gaseous olefins in the presence of a heterogeneous catalyst to produce upgraded bio‐oil. The influence of reaction conditions such as reaction time, reaction temperature, and catalyst content were evaluated. Physical and chemical properties such as acid value, higher heating value, water content, and optimal conditions were identified. The result of olefination shows improved bio‐oil quality and increased energy density. Accelerated aging tests were also performed. © 2014 American Institute of Chemical Engineers Environ Prog, 2014 34: 933–941, 2015